2020
DOI: 10.1186/s12870-020-02571-5
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and Transcriptome characterization of an endemic species of Vietnam, Panax vietnamensis Ha et Grushv., including the development of EST-SSR markers for population genetics

Abstract: Background: Understanding the genetic diversity in endangered species that occur inforest remnants is necessary to establish efficient strategies for the species conservation, restoration and management. Panax vietnamensis Ha et Grushv. is medicinally important, endemic and endangered species of Vietnam. However, genetic diversity and structure of population are unknown due to lack of efficient molecular markers. Results: In this study, we employed Illumina HiSeq™ 4000 sequencing to analyze the transcriptomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 93 publications
0
17
1
Order By: Relevance
“…Recently, 123 SSRs were identified in the A. tsaoko chloroplast genome; the mean density of SSR loci is up to 1/1.33 kb; however, they have not been validated for A. tsaoko [ 48 ]. In recent years, the use of transcriptome data to obtain sequences containing microsatellites, and the study of their genetic diversity has been successfully reported [ 52 54 ]. Excluding mononucleotide repeats, trinucleotides were found to be the most abundant repeats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 123 SSRs were identified in the A. tsaoko chloroplast genome; the mean density of SSR loci is up to 1/1.33 kb; however, they have not been validated for A. tsaoko [ 48 ]. In recent years, the use of transcriptome data to obtain sequences containing microsatellites, and the study of their genetic diversity has been successfully reported [ 52 54 ]. Excluding mononucleotide repeats, trinucleotides were found to be the most abundant repeats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is no difference between cultivated individuals and those found in the wild. High genetic diversity and gene flow between P. vietnamensis populations have recently been attributed to insect dispersal (Vu et al, 2020 ). Strong gene flow and insufficient splitting time between cultivated populations has also been observed for P. notoginseng (Pan et al, 2016 ), and was attributed to non-random mating among the individuals of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the differentiation between P. vietnamensis and P. ginseng (Vasyutkina et al, 2018 ). Studies on P. vietnamensis continue to shed new light on intra- and interspecific evolutionary relationships (Nguyen et al, 2020 ; Vu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study provided a basis for further research on S. oleoides. Dinh et al (2020) used the Illumina HiSeq 4000 sequencing platform to analyze the transcripts (from roots, leaves, and stems) of Populus alba. A total of 11,343 EST-SSRs were detected, and 101 primer pairs were screened from 7,774 pairs for polymorphism verification.…”
Section: Development Of Molecular Markers Based On Transcriptome Sequencingmentioning
confidence: 99%